COMBINATION OF DOCUMENTATION, ANIMATION, AND LIVE ACTION IN THE FILM PINK PASTEL - Biosa, Sito Fossy; Marianto, M. Dwi (Seni Media Rekam ISI Surakarta, 2020)
Film Pink Pastel with visual documentation, animation and live action (called Trisikon; three situation and condition) is used in response to the dangerous phenomenon of ‘idam pica’ (pica cravings). The writer tried to make a film that is not a cliché, not just a play of dramaturgy, gesture, mimic, and exploratory dialogue from the actor himself. The author explored the visual (mise en scene) by dissecting cliches and not cliches artwork. All action ranging from phenomena, maternal ecstasy, to visual realization. It is intended to create random Audio visual spaces, chaotic, and broken. The combination of documentation, animation, and live action in this film is able to realize the Deleuze’s Logic Sensation theory, that there were two powers owned by chaos at the same time, destructive power, and life power. The modified form in the film Pink Pastel can help the filmmakers to open the possibility of wider cinema visual.